State Capacities and Regulation in Public-Private Partnerships: Challenges for the New Development Strategies - Freigedo, Martín; Fuentes, Guillermo; Milanesi, Alejandro (Revista del CLAD Reforma y Democracia, 2015)
The concept of state capacities has been extensively studied. Yet, despite the successive conceptualizations made -especially in Latin America- it still suffers from a number of shortcomings. While progress has been made, there are still some gaps to adequately differentiate the types of capacities needed depending on the political objectives that are sought. Also, much of the work on this issue points to a single capacity of the public actor regardless whether it is a direct provider or a regulator. The state capacities to fulfill either function are not equal. So, it is understood here that the traditional approach becomes static, with limits to induce analytical elements that help to understand new phenomena. These difficulties are particularly relevant in the current situation of the region characterized by the building of new national development models which logic implies greater public-private cooperation. Faced with this problem, the article seeks to bring elements to the debate on state capacities, by identifying new analysis dimensions focused on the political dimensions of regulatory capacities that can be taken in future studies whether to build new categories or re-discuss the existing production.
Keywords: State Capacities; Regulation; Public-Private Partnership